Journal of Echocardiography - Tanabe, Kazuaki; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
The Journal of Echocardiography, the official journal of the Japanese Society of Echocardiography, publishes work that contributes to progress in the field and articles in clinical research as well, seeking to develop a new focus and new perspectives for all who are concerned with this discipline. The journal welcomes original investigations, review articles, letters to the editor, editorials, and case image in cardiovascular ultrasound, which will be reviewed by the editorial board. The Journal of Echocardiography provides the best of up-to-date information from around the world, presenting readers with high-impact, original work focusing on pivotal issues.
Keywords: Radiology; Cardiology; Cardiology; Ultrasound; Imaging / Radiology